Bond Behavior Between Steel Bar and Reactive Powder Concrete Under Repeated Loading - Dewen Zhang; Yanming Feng; Ruihui Han; Xiangsheng Kong; Dehong Wang; Chao Ren (Buildings)
To investigate the influence of repeated loading on the bond behavior between steel bars and reactive powder concrete (RPC), this study conducted repeated loading tests on eight beam specimens and one static loading test as a control. The effects of stress levels and the number of repeated loading cycles on the bond behavior between steel bars and RPC were examined. The results indicate that the static failure mode was characterized by steel bar pull-out accompanied by significant plastic deformation, with no propagation of cracks in the RPC after their initiation, demonstrating the excellent crack control capability of RPC. After 10,000 cycles of repeated loading at a high stress level (Z = 0.9), the ultimate bond strength decreased by only 3.68%, indicating the superior fatigue resistance of the steel–RPC interface. Based on the analysis of slip accumulation effects, a constitutive model considering stress levels and the number of repeated loading cycles was established. This model can serve as a basis for the design of steel anchorage in RPC structures subjected to cyclic loading.